Penyelenggaraan Pertanian Lahan Pantai Dan Dampaknya Terhadap Lingkungan Di Propinsi Daerah Istimewa Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Increasing number of agricultural land with function shifted into different sector other than agriculture has created its expansion to marginal land, i.e. coastal land. Coastal land are area susceptible to changes due to specific activities in that area. Therefore, coastal land exploitation for agricultural activities should be carried out in such a way that its exploitation do not damage coastal land environment. Results of the research indicate that efforts on establishing environmental-oriented sustainable agriculture had been already conducted, but it had not been maximal yet due to various impediments. Effort that government made was to set up reservation and cultivation areas within Regional Spatial Plan and Detailed Spatial Plan for South Coastal Area. The Regional Spatial Plan and Detailed Spatial Plan for South Coastal Area, however, did not confirm whether agricultural activities were allowed to be cond ucted in reservation area of coastal border. On the other hand, the community had not received sufficient knowledge on reservation and cultivation available in coastal area. In addition, government also issued policy on environmental-friendly irrigation system. However, it had not been maximally implemented yet due to limited fund. Positive impact on environment is increasing reforestation in coastal area. Negative impact imposed is the possibility of sea-water intrusion into land due to excessive ground water exploitation. Positive impact on public social condition is additional alternative income and more greater communality and higher mutual cooperation among peasants. Its negative impact is uncontrolled parceling of land, Agricultural implementation on coastal land, on one hand, supported Sustainable Coast Program in Yogyakarta Special Region Province in term of reforestation along coastal area. On the other hand, no deeper study was conducted viewed based on environmental aspect, especially in term of impact aspect.